The Fate of Employees of the Lithuanian Forest Industry 1939–1953 - Brukas , Algirdas (Genocidas ir rezistencija, 2012)
The article explores the fate of employees of the Lithuanian State Forest Industry, a separate branch of the economy, between 1939 and 1953, the staffing policy in this industry and specific features and results of its implementation. The forest was the location closely associated with the post-war resistance struggle, because a large number of partisan headquarters and hideouts were located in the forests. As a result, the work of forestry professionals and foresters and their attitude to events of that time were very important both to resistance fighters and the occupational government structures. The majority of them were under pressure to ‘double deal’, with the result that many left their jobs voluntarily as such conditions were not acceptable to them. The article explores all the events related to the turnover and fate of staff in chronological order: their deaths due to all possible reasons, including at the hands of their own partisans or the collaboration of foresters with the Nazis and the Soviet forces; various reprisals – from deportations and labour camps to violence; emigration to the west and the east due to political reasons; repatriation; peculiarities of employment of people who returned after deportation and imprisonment; the extent of employment of staff of Russian and other nationalities in the post-war years in the Lithuanian forestry system, etc. If the number of full time employees of the industry at the beginning of the Second World War (3,900 people) is held as a point of reference, major losses of the industry can also be expressed in the following figures: one in every eleven employees of this industry was killed; one in four employees suffered reprisals and were sentenced for various periods of time; and one in three suffered physical or moral violence. In the post-war years, only 75 Russian-speaking employees were recruited to the Lithuanian State Forest Industry and after Stalin’s death, over 1,000 of people who returned after deportation and imprisonment were employed.